The Impact of Vocational Education Curriculum on Employability of Electrical Graduates: A Systematic Literature Review - Muhammad Zidan Fathulloh; Rahmatul Irfan; Didik Hariyanto (FKIP - Universitas Riau, 2026)
Electrical This systematic review synthesizes empirical evidence on teaching and learning innovations in electrical engineering and Technical and Vocational Education and Training (TVET) published between 2021 and 2025. The study aimed to identify effective pedagogical approaches, assess technology integration outcomes, and map research gaps. Following the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta Analyses) guidelines, a systematic search of Scopus, Google Scholar, and specialized TVET journals yielded 1,247 initial records. After screening against inclusion criteria (empirical studies, electrical engineering TVET context, 2021-2025), 54 studies were included for synthesis. Results revealed three dominant pedagogical themes: project based learning (PBL) and cooperative models (26% of studies), flipped classroom approaches (19%), and simulation based learning including immersive VR (24%). Technology enhanced learning showed significant improvements in factual knowledge (Cohen's d ranging from 0.76 to 1.63) but inconsistent effects on higher order thinking skills and knowledge transfer. Key gaps identified include insufficient longitudinal studies (only 11% > 6 months), lack of standardized HOTS assessment instruments, weak industry curriculum alignment, and minimal focus on soft skill integration. The review concludes that while innovative pedagogies improve short term outcomes, there is an urgent need for longitudinal research, industry linked curriculum development, and validated transfer assessment tools.